Joint application of antimicrobial agents on microbial flora chilled meat cattle : Use of mathematical models - Álvarez, María Cecilia (2016)
Objectives of this work were: i) to study the effect joint application of antimicrobial agents on microbial flora chilled meat cattle; ii) to model mathematically this microbial growth and iii) validate the models with own experimental results. Samples were irradiated with UVC light for 5 minutes and then were added a solution of oregano oil and lactic acid (1: 1). Untreated samples were considered as control. Gompertz model was appropriate to quantify microbial growth in all conditions studied. Meanwhile, Pseudomonas sp in treated samples showed no development, having to apply the linear regression model.